Potentiostatic transients related to the electrolytic oxidation of KSCN and mixtures of NaSCN + KSCN melts on polycrystalline platinum - Vásquez Moll, Víctor Dennis (1985)
Potentiostatic transients related to the electrolytic oxidation of molten thiocyanate (KSCN and KSCN + NaSCN, 0.7:0.3 mol/mol) on polycrystalline Pt obtained in the 168–290°C range are interpreted in terms of a nucleation and growth mechanism under diffusion control which involves the formation of two different products constituting the passivating anodic layer. The different adjustable parameters are compatible with the possible molecular structure of the anodic layer.